Short-horizon incentives and stock price inflation - Chi, Jianxin Daniel; Gupta, Manu; Johnson, Shane A. (Journal of Corporate Finance, 2020)
Do managerial incentive horizons have capital market consequences? We find that they do when short-sale constraints are more binding. Firms experience significant stock price inflation when their CEOs have short horizon incentives. The short-horizon CEOs sell more shares at inflated prices and generate greater abnormal trading profits. The stock price inflation is partly explained by greater earnings surprises and more positive investor reaction to the surprises. To inflate stock prices, short-horizon firms are more likely to employ income-increasing discretionary accruals. Consistent with theoretical predictions, all these effects are attenuated or statistically insignificant when short-sale constraints are less binding.